The role of male's anal horns in copulation of a scorpionfly. (13th November 2014) - Zhong, Wen; Ding, Guo; Hua, Baozhen
Abstract Sexual conflict drives evolution of sexually antagonistic adaptations that give advantages to the bearer. As a consequence of sexual conflict, male scorpionflies (Mecoptera: Panorpidae) provide nuptial gifts for the female and use grasping organs to repress female resistance. These organs, except notal organ, have not been satisfactorily studied. In this paper, the mating behavior of Dicerapanorpa magna (Chou) was investigated to reveal the role of the anal horns (a pair of posterior processes on tergum VI) of males. The males initiate copulation through grasping the female with the notal organ and anal horns, prolonging copulation by providing salivary masses to the female as nuptial gifts and maintaining copulation after the female consumed the salivary masses. The results of a manipulative experiment show that the anal horns play a significant role in the mating success for the males of D. magna by promoting male domination in copulation through increasing the duration of pre‐ and post‐gift‐providing copulatory stages against female resistance and by avoiding wasting of nuptial gifts. The anal horns of male D. magna seem to be a male adaptation evolved to overcome female mating resistance.